The Effect of Exercise Using A Float And Leg Length On The Results Of The 50 M Breaststroke Swimming Speed - Mochamad Rifa’i; Sri Sumartiningsih; Agung Wahyudi (JUARA : Jurnal Olahraga, 2022)
The purpose of this study was to determine the effect of using a buoy on the results of the 50-meter breaststroke swimming exercise, to determine the difference in the effect of high, medium and low leg length on the results of the 50-meter breaststroke swimming exercise for beginners KU IV Club Spectrum Semarang. This research method is experimental with a 3x3 design sample of 29 novice athletes for the pretest. The highest and lowest results were omitted, so a sample of 27 KU IV novice athletes was taken by purposive sampling. The instrument for the test is to provide exercise treatment using a pull buoy, fishing net and board. Associated with the length of the category of leg length are high, medium and low. The results showed (1) There was a significant difference in the effect of the results for students who used a pull buoy, fishing net, or board in the 50-meter breaststroke swimming exercise (2) There was a significant difference in results for students with high, medium, and long leg lengths. low in the 50-meter breaststroke. (3) There is no interaction between the legs' length and the buoy type in determining the results of the 50-meter breaststroke swimming exercise. Conclusion: The fishing net buoy results are more significant than using the board buoy and pull buoy; it can be seen that the average result is 56.67 seconds, compared to the pull buoy 72.33 seconds and the board buoy 72.33 seconds. Leg length in the high category has more significant results than in the medium and low leg length category; there is no interaction between leg length and the type of buoy in the 50-meter breaststroke swimming speed results..